The human brm protein is cleaved during apoptosis: The role of cathepsin G - Biggs, Joseph R. (The National Academy of Sciences, 2001)
The human brm (hbrm) protein (homologue of the Drosophila melanogaster brahma and Saccharomyces cervisiae SNF-2 proteins) is part of a polypeptide complex believed to regulate chromatin conformation. We have shown that the hbrm protein is cleaved in NB4 leukemic cells after induction of apoptosis by UV-irradiation, DNA damaging agents, or staurosporine. Because hbrm is found only in the nucleus, we have investigated the nature of the proteases that may regulate the degradation of this protein during apoptosis. In an in vitro assay, the hbrm protein could not be cleaved by caspase-3, -7, or -6, the “effector” caspases generally believed to carry out the cleavage of nuclear protein substrates. In contrast, we find that cathepsin G, a granule enzyme found in NB4 cells, cleaves hbrm in a pattern similar to that observed in vivo during apoptosis. In addition, a peptide inhibitor of cathepsin G blocks hbrm cleavage during apoptosis but does not block activation of caspases or cleavage of the nuclear protein polyADP ribose polymerase (PARP). Although localized in granules and in the Golgi complex in untreated cells, cathepsin G becomes diffusely distributed during apoptosis. Cleavage by cathepsin G removes a 20-kDa fragment containing a bromodomain from the carboxyl terminus of hbrm. This cleavage disrupts the association between hbrm and the nuclear matrix; the 160-kDa hbrm cleavage fragment is less tightly associated with the nuclear matrix than full-length hbrm.